The concept of legal interest in contentious proceedings before the AfricanCourt on Human and Peoples’ Rights - (:unkn) unknown (My University, 2023)
In contentious matters, some explicit provisions of the Protocol to theAfrican Charter on Human and Peoples’ Rights on the Establishment of an AfricanCourt on Human and Peoples’ Rights and the Rules of Procedure of the Court definethe procedural preconditions for submitting an application before the Court. Theseprovisions also set out the essential criteria for intervention in a pending case. In theimplementation of the right to submit an application and intervention, the concept oflegal interest comes into play. With the aim of strengthening the position of thedrafters of the African Court’s Protocol and the Rules of the Court, and to compensatefor the imperfections of the observations of certain states, this contribution discussesthe concept of legal interest. It argues that legal interest is immaterial to thesubmission of application before the Court. However, during proceedings, theparticipation certain parties is subjected to their demonstrating they have legal interest. The rigid application of the concept of legal interest may be a hindrancenonetheless to the participation of a category of parties. Although the Court’sjurisprudence demonstrates the Court’s willingness to ensure broader participation inproceedings, the current state of scholarship does not sufficiently highlight thisparticularity of the African Court on Human and Peoples’ Rights system.
Keywords: African Research